Reverse Technology Transfer from the East to the West – Evidence from R&D sites of Western Multinationals in China - Wolfram, Pierre; Agarwal, Nivedita; Brem, Alexander (European Journal of Innovation Management, 2018)
Purpose The approach of Western companies to internationalise their R&D by establishing R&D sites in emerging markets (EMs) has led to a discussion about the role of R&D in home markets and host markets. The purpose of this paper is to shed light on the evolution of foreign R&D sites of Western companies in EMs and their role using China as the empirical context. Design/methodology/approach The study uses the State Intellectual Property Office database, and investigates about 2,000 patent families of the top 14 Western patent applicants in China. Findings The results indicate a gradual shift from an exploitative to an exploratory role of R&D sites in China. The study also shows evident learning effects on Western R&D from local counterparts. Research limitations/implications The paper motivates further research of R&D internationalisation approaches within EMs, and explores the changing role of local subsidiaries. While the study is only focussed on China, the applicability of the results is limited in context of other countries, due to cultural, economic and legislative differences. Practical implications This study shows the increasing importance of EMs such as China and how these markets, known for imitations and cheap resources, are gradually moving towards innovations and creating new technologies locally. Originality/value Based on the patent analysis, this study shows the growing importance of the local R&D subsidiaries of Western multinationals in Chin
Keywords: Technology transfer; International business; Reverse technology transfer